The impact of the insurance sector on the Algerian economy - MOKADEM, Abdelilah; GUEDDAL, Zineddine (Journal of Human Sciences, 2020)
The insurance market in Algeria is not yet saturated, it represents less than 1% of PIB, despite it growths slowly, it is evolving from one year to the next, with this research, we will try to treat the elements of the national market, which are dominated by the public sector compared to the private sector and the weakness of the personal insurance sector, which is dominated by automobile insurance, which makes bets for the future based on the strengthening of other sectors, in addition to giving more weight to specialized insurance, reinsurance, and this in parallel with the policy of the State in the diversification of the economy.